2014
DOI: 10.1038/npp.2014.34
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association Analysis of 300 Genes Identifies a Risk Haplotype in SLC18A2 for Post-traumatic Stress Disorder in Two Independent Samples

Abstract: The genetic architecture of post-traumatic stress disorder (PTSD) remains poorly understood with the vast majority of genetic association studies reporting on single candidate genes. We conducted a large genetic study in trauma-exposed European-American women (N ¼ 2538; 845 PTSD cases, 1693 controls) by testing 3742 SNPs across more than 300 genes and conducting polygenic analyses using results from the Psychiatric Genome-Wide Association Studies Consortium (PGC). We tested the association between each SNP and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 46 publications
3
51
0
Order By: Relevance
“…We used the standard polygenic scoring approach (Purcell et al, 2009) with results from the PGC for MDD, BP, and SCZ (Cross-Disorder Group of the Psychiatric Genomics Consortium and Genetic Risk Outcome of Psychosis Consortium, 2013) and found that PTSD diagnosis was predicted by risk scores derived from BPD, but not from MDD or SCZ. Our results for BPD reached significance at p-value thresholds >0.3 from the original GWAS, similar to the PTSD candidate gene study (Solovieff et al, 2014). Pleiotropic effects across a range of psychiatric disorders have recently been reported (Cross-Disorder Group and Genetic Risk Outcome, 2013) and provide exciting new insights into the genetic architecture of PTSD and other psychopathologies.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…We used the standard polygenic scoring approach (Purcell et al, 2009) with results from the PGC for MDD, BP, and SCZ (Cross-Disorder Group of the Psychiatric Genomics Consortium and Genetic Risk Outcome of Psychosis Consortium, 2013) and found that PTSD diagnosis was predicted by risk scores derived from BPD, but not from MDD or SCZ. Our results for BPD reached significance at p-value thresholds >0.3 from the original GWAS, similar to the PTSD candidate gene study (Solovieff et al, 2014). Pleiotropic effects across a range of psychiatric disorders have recently been reported (Cross-Disorder Group and Genetic Risk Outcome, 2013) and provide exciting new insights into the genetic architecture of PTSD and other psychopathologies.…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, the large MRS GWAS was able to replicate a recent finding from a candidate gene study including 300 genes (Solovieff et al, 2014) that demonstrated for the first time the existence of common SNPs between PTSD severity and bipolar disorder based on cross-disorder polygenic risk score analyses. We used the standard polygenic scoring approach (Purcell et al, 2009) with results from the PGC for MDD, BP, and SCZ (Cross-Disorder Group of the Psychiatric Genomics Consortium and Genetic Risk Outcome of Psychosis Consortium, 2013) and found that PTSD diagnosis was predicted by risk scores derived from BPD, but not from MDD or SCZ.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations